UM OLHAR JURÍDICO SOBRE OS BENEFICIOS DO SISTEMA DE PREVIDÊNCIA COMPLEMENTAR VIGENTE NO BRASIL - Ataíde Cápua Cápua, Valdeci (LINKSCIENCEPLACE, 2026)
Brazilians are old records about the search for the man for protection and social support through mutual assistance throughout history , what causes why this work is substan tially address the current private pension system in Brazil whose larger mission is guided on the supply of the gaps left by the public system and national security . Therefore, your goal is based on checking the actual benefits brought to the member and p articipant of the current private pension system deepening their legal nature to bring the light of the discussion of this branch of the Social Security Law insusceptible points of administrative reforms under and legal system for the current Brazilian pen sion fund . Following an approach by the paths taken up here by pension plans , mister is made to analyze the effectiveness of this system , given the current economic scenario of the country through the comparison of data and existing realities to establi sh whether its objectives are being achieved and proved effective .